Mechanistic insights into neutrophil involvement in liver transplant ischemia-reperfusion injury and rejection - She, Zhipeng; Cai, Hailun; Li, Xinqiang; Chen, Jinhui; Chen, Ying; Cai, Jinzhen; Wu, Bin (Frontiers in Immunology, 2026)
Ischemia-reperfusion injury (IRI) and subsequent rejection remain the paramount pathological barriers to long-term graft survival following liver transplantation. Traditionally viewed as mere ‘first responders’ in the acute inflammation of IRI, neutrophils are now recognized, based on recent advances, as pivotal regulators that bridge innate and adaptive immunity throughout the entire post-transplant course. This review aims to systematically delineate the dual pathological mechanisms of neutrophils in both IRI and rejection post-LT. During the initial phase of IRI, we focus on the robust activation of neutrophils, driven by damage-associated molecular patterns (DAMPs), with a particular emphasis on the formation of neutrophil extracellular traps (NETs). NETs act not only as key effectors causing sinusoidal microcirculatory dysfunction and direct hepatocellular injury, but their released histones and proteases also serve as potent danger signals, amplifying the local inflammatory cascade. The central thesis of this review is that the inflammatory microenvironment, orchestrated by neutrophils during IRI, provides the essential immunological substrate for subsequent rejection. We delve into the mechanisms by which neutrophils bridge to adaptive immunity: NETs serve as a scaffold for autoantigens, activating B cells and promoting the production of donor-specific antibodies (DSA), thereby driving antibody-mediated rejection (AMR). Concurrently, chemokines released by neutrophils efficiently recruit effector T cells and, through interactions with antigen-presenting cells, exacerbate cell-mediated rejection (CMR). Finally, we prospect future therapeutic directions, emphasizing that targeting common pathways within this ‘injury-immunity’ axis—such as inhibiting DAMP release, blocking NET formation, or employing pro-resolving mediators to actively terminate inflammation—represents a pivotal strategy to break the vicious cycle of IRI and rejection and achieve long-term immune tolerance.